(untitled) (At-Tibyan, 2023)
Quraish Shihab argues that in Islam sex is not something dirty and unclean, Allah commands it and it is written in his Word, but some recent dedakes there are issues that state that women are male sex objects and make these religious texts to support their ideology of treating women arbitrarily, especially in the sexual affairs of her husband. This research is a type of literature with a qualitative method that is descriptive-analytical, with a linguistic approach this research uses many sources of books, nahwu books, and tafsir books that have a linguistic character In analyzing the data, this research uses content analysis, which is a symbolic research method on the messages of the Qur’an text. In this case the content analysis used is semantic content analysis to analyze Qs.al-Baqarah: 223. The findings in this study are the use of the word Anna in this verse is the center of information about the procedures in conducting conjugal relations, the existence of Anna in this verse also shows the flexibility of the meaning of the verse and the Qur’anic respect for women through the redaction arrangement. In the aspect of procreation, the flexibility of the meaning of Anna< in this verse shows Allah’s glorification of women’s rights and obligations in the family and religion, by providing restrictions not to carry out sexual exploitation at the wrong time, place, and way. Understanding the Qur’an by reviewing its linguistic or stylistic aspects can limit the individual interests of the mufasir because understanding will be related to the I’jaz al-lughawi al-Qur’an. Anna< in this verse is the meaning of taswiyah (equating something with something), this shows the use of narratives like this is to adjust the habits of Arab society that conveys messages with figurative language. In addition, there is a further explanation of the recommended procedure, time and place as explained in the book of quratul ’uyun, the Anna symbol illustrates how Islam greatly glorifies and respects wives/women, and this can dismiss the perception that women are only as lust satisfiers, this kind of thinking will have an impact on the treatment of husbands/partners who are arbitrary